Self Regulation Siswa Di Era Globalisasi Refleksi Bagi Generasi Milenials - Sumarwiyah Sumarwiyah; Masturi Masturi; An Nisa Nur Afifah; Ariba Seila Dina (Jurnal Prakarsa Paedagogia, 2018)
Self regulation is a process that activates thoughts, behaviors, and feelings that are continuous in an effort to achieve a set goal. Millennial generation is a group of young people born between 1980 and 2000 in very rapid technological developments. Reflection on self regulation in the millennial generation is very appropriate to implement, because by reflecting millennial generations it can be easier to improve selfregulation optimally. When millennials have positive regulations and are balanced with technological advances, they can form a generation that is a positive generation. By way of reflection selfregulation the millennial generation can control or manage themselves which includes cognitive, affective, and psychomotor aspects, so that it can become a millennial generation that can utilize social media well.